1991
DOI: 10.1073/pnas.88.24.11202
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the initial charge separation in bacterial photosynthetic reaction centers.

Abstract: The initial electron tranfer in reaction centers from Rhodobacter sphaeroides R26 was studied by a subplcosecond transient pump-probe technique. The measured kinetics at various wavelengths were analyzed and compared with several mechanisms for electron tra er. An unambiguous determination of the initial electron transfer mechanism in reaction centers cannot be made by studying the anion absorption region (6404690 nm), due to the spectral congestion in this region. However, correlations between the stimulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
78
0
2

Year Published

1992
1992
2002
2002

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(87 citation statements)
references
References 36 publications
7
78
0
2
Order By: Relevance
“…Very recent emission experiments have shown that the 3 ps decay of P* seems to be a biphasic process with two time constants [8,9]. At all temperatures an additional subpicosecond component was detected in Rhodobacter sphaeroides having time constants of 0.3 ps to 0.9 ps for temperatures of 25 K to 300 K [10,11]. The same ultrafast component was found in RCs from Rhodopseudomonas viridis having a time constant of 0.65 ps at 300 K [5].…”
Section: Introductionmentioning
confidence: 73%
“…Very recent emission experiments have shown that the 3 ps decay of P* seems to be a biphasic process with two time constants [8,9]. At all temperatures an additional subpicosecond component was detected in Rhodobacter sphaeroides having time constants of 0.3 ps to 0.9 ps for temperatures of 25 K to 300 K [10,11]. The same ultrafast component was found in RCs from Rhodopseudomonas viridis having a time constant of 0.65 ps at 300 K [5].…”
Section: Introductionmentioning
confidence: 73%
“…Photoexcitation is followed by the transfer of an electron to a distant bacteriopheophytin HL (Fig. 2) with time constant equal to about 3 ps and with quantum yield that approaches unity (3)(4)(5)(6)(7). It is now accepted that this fast long-range electron transfer is mediated by an accessory bacteriochlorophyll monomer BL whose reduced state couples to those of the excited special pair and the bacteriopheophytin.…”
mentioning
confidence: 99%
“…However, the energetics of the accessory chlorophyll, as well as the mechanism of the process, are still under debate . Time-resolved experiments on wild-type reaction centers (3)(4)(5)(6) have failed to detect a reduced accessory chlorophyll state and concluded that the population of this state remains small throughout the charge transfer. If the chlorophyll monomer is involved via a sequential mechanism, this behavior is possible if the second step is much faster than the first.…”
mentioning
confidence: 99%
“…The observation of an additional, subpicosecond time constant in Rhodobacter sphaeroides (16)(17)(18)(19)(20) again raised the possibility of P+B-being a real intermediate according to P .…”
mentioning
confidence: 99%